2001
DOI: 10.1097/00000374-200104000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Ethanol Consumption on Protective T-Helper 1 and T-Helper 2 Immune Responses Against the Parasites Leishmania major and Strongyloides stercoralis in Mice

Abstract: Mice maintained on an ethanol-containing liquid diet had some alteration in their ability to produce Th1 and Th2 immune responses yet were capable of generating unimpaired protective Th1 and Th2 responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, chronic EtOH ingestion seems to have significant effects on phenotypic and functional T cell subsets including reduced total numbers, increased CD4/CD8 ratios, and an increase in the memory:naïve phenotype ratio (Gurung et al., 2009; Young et al., 2008). Other studies suggested a decrease in Th1 immunity and an increased Th2 response in a murine model of parasitic infestation (Krolewiecki et al., 2001). In a model examining T cell responses to listeria monocytogenes, it was found that EtOH ingestion has little effect on antigen‐specific CD4 cells but causes significant reduction in antigen‐specific CD8 T cells (Gurung et al., 2009).…”
Section: Discussionmentioning
confidence: 92%
“…However, chronic EtOH ingestion seems to have significant effects on phenotypic and functional T cell subsets including reduced total numbers, increased CD4/CD8 ratios, and an increase in the memory:naïve phenotype ratio (Gurung et al., 2009; Young et al., 2008). Other studies suggested a decrease in Th1 immunity and an increased Th2 response in a murine model of parasitic infestation (Krolewiecki et al., 2001). In a model examining T cell responses to listeria monocytogenes, it was found that EtOH ingestion has little effect on antigen‐specific CD4 cells but causes significant reduction in antigen‐specific CD8 T cells (Gurung et al., 2009).…”
Section: Discussionmentioning
confidence: 92%
“…However, it seems that helper T cell type 2 (TH2) immune response is not impaired by the consumption of ethanol [18], [19]. Mice chronically treated with ethanol presented normal response to larvae of S. stercoralis inoculated into chambers implanted in the subcutaneous tissue [20]. For these reasons it is difficult to pin point immunosuppression induced by ethanol as the major factor for the increased prevalence of Strongyloides in chronic alcoholics, because the TH2 response, the most important resistance against this worm in humans [21], [22], is not depressed by ethanol abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between hookworms and S. stercoralis has been examined and confirmed by 2 recent epidemiologic studies, highlighting the common infectious route of these species that access the human host through larval penetration of intact skin 7,8 . The relationship between age and intensity of prevalence demonstrates for S. stercoralis an age distribution similar to hookworms 24 , with prevalence rising rapidly during the first 20 years with a slower but continued increase in prevalence through adult life 5,[25][26][27] . Other risk factors, initially considered to be associated with an increased risk for clinically severe disease, such as HIV or HTLV-1 infection and alcoholism have also been found to be more frequently associated with acquisition of infection 28,29 , although in the case of alcohol abuse, the risk might be linked to malnutrition rather than pure toxicity due to ethanol itself 30 .…”
Section: Transmissionmentioning
confidence: 99%